PEMANFAATAN PELEPAH SAWIT UNTUK PAKAN FERMENTASI KAMBING, MODEL PERTANIAN SIRKULAR DI TANAH LAUT - Febrina, Bunga Putri; Maulana, Fajri; Yardani, Jesi; Agasi, Satri Yusasra; Fajri, Fadhli; Cahayati, Khaida Putri; Andini, Elliani Cahya; Khoiriyah, Siti Nur (Universitas Mataram, 2025)
Oil palm plantation waste, including fronds, fibres, and palm kernel meal, remains an underutilised local resource among livestock farmers in the Tanah Laut region. Despite its potential as an economical and sustainable alternative feed, its adoption has been limited. This community service initiative, conducted in collaboration with ASPERKAM Tanah Laut, aims to promote a circular agriculture model by utilising oil palm waste as feed for goats. The primary objective is to enhance farmers’ capacity to process oil palm waste into nutritious livestock feed while strengthening community-based sustainable agricultural practices. The implementation methods included field surveys, technical training on feed formulation, and feeding trials with goats. A participatory approach was employed to ensure active farmer involvement throughout each phase of the activity. The results indicate that oil palm waste can be processed into feed with adequate nutritional content and is well accepted by livestock. Feed cost efficiency improved by up to 30% compared to commercial feed. Farmers demonstrated increased knowledge and skills in feed formulation, along with heightened environmental awareness through organic waste reduction. This initiative also reinforced synergy between academia and local communities in developing grassroots innovations. In conclusion, the utilisation of oil palm waste as goat feed has proven to be effective and holds significant potential to support inclusive and sustainable circular agriculture.